2015
DOI: 10.1021/acsami.5b00209
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Lithium Electrodeposition with Pyrrolidinium-Based Ionic Liquid Electrolytes

Abstract: In this study, we report on the electroplating and stripping of lithium in two ionic liquid (IL) based electrolytes, namely N-butyl-N-methylpyrrolidinium bis(fluorosulfonyl) imide (Pyr14FSI) and N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr14TFSI), and mixtures thereof, both on nickel and lithium electrodes. An improved method to evaluate the Li cycling efficiency confirmed that homogeneous electroplating (and stripping) of Li is possible with TFSI-based ILs. Moreover, the presence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 50 publications
(87 reference statements)
1
84
0
1
Order By: Relevance
“…[79][80][81] The higher SEI formation potential observed for the former electrolyte may be ascribed to the FSI anion decomposition known to have enhanced film-forming ability compared to TFSI. 82 The second cycle, reported in the lower panel, reveals the exclusive presence of reversible peaks in the 0.0-0.2 V vs. Li/Li + region associated with the lithium uptake in the carbon working electrode, 83 thus suggesting the formation of a stable solid electrolyte interface (SEI) film with all the investigated electrolytes which prevents any further decomposition process during the following cycles. The anodic stability of the electrolytes is evaluated by measuring the current evolution during a stepwise potential sweep, increasing by 0.1 V each one hour, (Fig.…”
Section: 76mentioning
confidence: 95%
“…[79][80][81] The higher SEI formation potential observed for the former electrolyte may be ascribed to the FSI anion decomposition known to have enhanced film-forming ability compared to TFSI. 82 The second cycle, reported in the lower panel, reveals the exclusive presence of reversible peaks in the 0.0-0.2 V vs. Li/Li + region associated with the lithium uptake in the carbon working electrode, 83 thus suggesting the formation of a stable solid electrolyte interface (SEI) film with all the investigated electrolytes which prevents any further decomposition process during the following cycles. The anodic stability of the electrolytes is evaluated by measuring the current evolution during a stepwise potential sweep, increasing by 0.1 V each one hour, (Fig.…”
Section: 76mentioning
confidence: 95%
“…56 This is the first time that the amount of electrochemically deposited LmSs calculated from morphological information is directly correlated with the amount of external electron transfer measured electrochemically. Concerning the locations of preferential Li dissolution and LmS deposition during cycling it has been suggested that such locations are electrochemically more active 15 or possess a high local ionic conductivity. 27 It has been also suggested that a localized fracture in the SEI 58 Close-up inspection of morphological structures inside Li/Li-2 cell Apart from these findings, a close-up inspection of Figure 3 and 4 further demonstrates: 3) there are two different phases of electrodeposited LmSs, one being porous and the other solid and compact (both are shown in Figure 3b-e and 4c,f in light yellow and dark yellow, respectively, separated by a purple dotted line).…”
Section: Comparison Of the Amount Of Lms Determined By Morphological mentioning
confidence: 99%
“…67 The above-observed results agree well with previous simulations. 15,[68][69] Additionally, the direct internal view of the electrochemically short circuited Li/Li-2 cell suggests that the shutdown mechanism proposed by the sandwich structure can hardly provide any protection from a real ISC, i.e. the considerable force accompanied by the growing LmSs and the ISC-induced high Joule heating easily destroy the trilayer separator that is made by laminating PP and PE layers together by adhesion or welding.…”
Section: Comparison Of the Amount Of Lms Determined By Morphological mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides carbon, boron nitride137 and graphene138 serve as chemical and physical stable barriers to restrict the reaction with Li metal. Moreover, utilization of solid‐state electrolytes (such as polymer membranes) and the electrolytes with various additives (such as vinylene carbonate, Cs + and Rb + , LiF, lithium polysulfide, and ionic liquids) can serve as protective layers that also suppress the growth of lithium dendrites by providing an effective way for suppressing 139, 140, 141, 142, 143…”
Section: High‐capacity Anode Nanomaterials For Li‐ion Batteriesmentioning
confidence: 99%